PARADIGMA HUKUM ISLAM KLASIK DAN ALTERNATIF - Mohamad Ikrom (Indonesian Journal of Law and Islamic Law (IJLIL), 2019)
Islam is a universal religion, there is no limitation of place and time, therefore Islam should be accepted by every human being on this earth, without having to have "conflict" with the circumstances in which he is. Islamic jurisprudence is a discourse of thought to understand God's terms appropriately, to measure the extent of the freedom of a judge or faqih in determining the law. Muslims are ideologically grouped into four (4) models of social ideological paradigms, among others: Traditionalist Paradigm, Modernity Paradigm, Revival Paradigm; and the Transformation Paradigm. The typology of the Islamic legal paradigm is divided into three (3) major components, namely the Theological Paradigm; Linguistic Paradigm (Language), Methodological Paradigm. These paradigms then describe the characteristics of the study of fiqh which are generally characterized by several characteristics. First, epistemic characteristics, namely, (1) to some extent less separation between time and history, (2) univocalization of meaning, and (3) transhistorical (eternal) reasoning. Other characteristics are, (1) focusing on the study of Islamic law as law in the book, not including law in action, (2) complex branching of material, without paying attention to developing references. (3) polemic, and apologetic, (4) inward looking, and (5) atomistic approach.